B. F. SKINNER IS BACK. - PRASSAS, NIKOLAS (First Things: A Monthly Journal of Religion & Public Life, 2025)
The article focuses on B. F. Skinner's early work in behaviorism and his unusual World War II project to train pigeons as living missile-guidance systems. Topics include the origins and principles of behaviorism, the influence of Pavlov's conditioning experiments, and Skinner's development of operant conditioning as a foundation for modern behavioral science.